Prevention of Identity Politics Through Multicultural Education - Putri, Nimas Permata; Hendriyanto, Agoes (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The importance of multicultural education for journalists to serve as a capital in perceiving the reality of facts to shape media reality to build the opinion of the electorate. The research method used is qualitative research with Entman framing analysis. The data collection method uses documentation in the form of news text published by Pacitanku.com and Lintas7.net regarding candidates in the 2020 Pacitan Pilkada. Data analysis uses Entman framing analysis with emphasis, prominence, definitions, explanations, moral reasons, and text recommendations in news discourse. The results of local online media research with emphasis and prominence using identity politics such as; the brother of SBY, Nahdatul Ulama, Gagarin, a member of Nahdatul Ulama, the struggle of clerics with inspiration to build Pacitan, SBY founding father of the Democratic Party, Indrata Nur Bayuaji is similar to Indartato 2020. Local online media framing in perceiving the candidates for regent and deputy regent of Pacitan still uses identity to build public opinion. Increase electability and vote support of candidates. The need for multiculturalism education, especially in local online media as agents of reality construction, by prioritizing the construction of work performance and the quality of candidates. Local online media must become guardians of information to provide useful messages for the welfare of citizens to maintain the integrity of the Unitary State of the Republic of Indonesia by upholding diversity.